Darbepoetin‐alfa and intravenous iron administration after autologous hematopoietic stem cell transplantation: A prospective multicenter randomized trial. Issue 12 (30th September 2013) - Beguin, Yves; Maertens, Johan; De Prijck, Bernard; Schots, Rik; Seidel, Laurence; Bonnet, Christophe; Hafraoui, Kaoutar; Willems, Evelyne; Vanstraelen, Gaetan; Servais, Sophie; Jaspers, Aurélie; Fillet, Georges; et al.
Abstract : We conducted a randomized study analyzing the impact of darbepoetin alfa (DA) administration with or without intravenous (i.v.) iron on erythroid recovery after autologous hematopoietic cell transplantation (HCT). Patients were randomized between no DA (Arm 1), DA 300 μg every 2 weeks starting on Day 28 after HCT (Arm 2), or DA plus i.v. iron 200 mg on Days 28, 42, and 56 (Arm 3). The proportion achieving complete hemoglobin (Hb) response within 18 weeks (primary end point) was 21% in Arm 1 ( n  = 24), 79% in Arm 2 ( n  = 25), and 100% in Arm 3 ( n  = 23; P  < 0.0001). Erythropoietic response was shown to be significantly higher in Arm 3 ( n  = 46) than in Arm 2 ( n  = 50; P  = 0.008), resulting in lower DA use, reduced drug costs, and improved quality of life scores, but the effect on transfusions was not significant. In multivariate analysis, DA administration ( P  < 0.0001), i.v. iron administration ( P  = 0.0010), high baseline Hb ( P  < 0.0001), and low baseline creatinine ( P  = 0.0458) were independently associated with faster achievement of complete Hb response. In conclusion, DA is highly effective to ensure full erythroid reconstitution after autologous HCT when started on Day 28 post‐transplant. I.v. iron sucrose further improves erythroid recovery. Am. J. Hematol. 88:990–996, 2013. © 2013 Wiley Periodicals, Inc.